2021
DOI: 10.1186/s12711-021-00660-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of unique ROH regions with unfavorable effects on production and fertility traits in Canadian Holsteins

Abstract: Background The advent of genomic information and the reduction in the cost of genotyping have led to the use of genomic information to estimate genomic inbreeding as an alternative to pedigree inbreeding. Using genomic measures, effects of genomic inbreeding on production and fertility traits have been observed. However, there have been limited studies on the specific genomic regions causing the observed negative association with the trait of interest. Our aim was to identify unique run of homo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 42 publications
2
19
0
Order By: Relevance
“…The important economic traits of Duroc pigs are affected by strong artificial selection, which can lead to reduced polymorphism in regions near the selected areas due to linkage disequilibrium (LD). Previous literature ( Makanjuola et al, 2021 ; Zhao et al, 2021 ) reported that some homozygous regions had adverse effects on production and fertility traits in cattle, which may be caused by the increase of unfavorable alleles in LD with benefit alleles during intense selection. Therefore, maintaining genomic heterozygosity within commercial breeds is critical to the sustainability of livestock farming ( Williams et al, 2016 ), and ROHet may be a measure for investigating and managing the genetic diversity of Duroc populations in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The important economic traits of Duroc pigs are affected by strong artificial selection, which can lead to reduced polymorphism in regions near the selected areas due to linkage disequilibrium (LD). Previous literature ( Makanjuola et al, 2021 ; Zhao et al, 2021 ) reported that some homozygous regions had adverse effects on production and fertility traits in cattle, which may be caused by the increase of unfavorable alleles in LD with benefit alleles during intense selection. Therefore, maintaining genomic heterozygosity within commercial breeds is critical to the sustainability of livestock farming ( Williams et al, 2016 ), and ROHet may be a measure for investigating and managing the genetic diversity of Duroc populations in this study.…”
Section: Discussionmentioning
confidence: 99%
“…These provide excellent experimental materials for estimating the association between ROH and phenotypes. Considering that Howard et al ( 21 ), Martikainen et al ( 22 ), and Makanjuola et al ( 23 ) successfully detected unique ROH genotypes with adverse effects on the production and fertility traits of Landrace and Large White pigs, Finnish Ayrshire cattle, and Canadian Holsteins cow, respectively. We used the same HaploFinder software to identify unfavorable ROH genotypes within traits and across multiple traits.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that S21 had more total unfavorable ROHs on five traits than that of S22 population. According to previous description ( 23 ), stringent criteria with a significant threshold of FDR = 0.01 and at least 50 SNPs in a ROH were used to identify significantly unfavorable ROH regions in two Duroc lines. Although these options may ignore some valuable genotypes, the regions we detected were expected to be the most deleterious to the phenotypes and were formed in recent generations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations